Politics of Knowledge in Conservation: (De)valued Traditional Ecological Knowledge of Bote in Chitwan National Park, Nepal - Mani Rai, Indra; Kumar Dhakal, Rebat (Ethnobiology and Conservation, 2024)
Political ecology studies have mostly explored the conflicts that arise between local communities and Indigenous peoples' (IPs') vulnerability to sustainable livelihoods based on nature and conservation regimes. Even in the context of the change in conservation tactics towards active community involvement and socioeconomic development, which has reinforced the fortress conservation strategy, traditional ways of life and the lived traditional ecological knowledge (TEK) of IPs are under jeopardy. Nevertheless, the studies give little consideration to the way in which TEK is (de)valued for bolstering fortress conservation at the expense of IPs' livelihoods unsustainability. This study investigates the (de)valuation of TEK of Bote embedded in their traditional livelihoods through conservation management, based on a critical ethnographic investigation carried out in two villages of Bote IPs (in the Buffer Zone area) of Nawalparasi district of Chitwan National Park (CNP) –southern lowlands of Nepal. We argue that TEK is paralyzed by a conservation regime without acknowledging the symbiotic relationship between IPs and biodiversity. Therefore, in order to conserve biodiversity and support the mutual sustainability of biodiversity and local livelihoods, there needs to be active guardianship and stewardship of IPs.